CYSTICERCUS BOVIS INDUCED HEMATO-BIOCHEMICAL CHANGES IN CATTLE AND BUFFALOES - M. Saeed; A.Z. Durrani; M.A. Khan; A. Maqbool; M. Avais; M.Younus; A. I. Aqib; I. Ahmad; M. Ijaz (Journal of Animal and Plant Sciences, 2016)
Cysticercosis is an infection of muscles in cattle and buffaloes, which occurs due to the larval stage of Taenia saginata. Cysticercosis has worldwidedistribution but is more common in developing countries due to poor hygienic measures.  Hematological and biochemical tests may be used as alternate for the diagnosis of cysticercosis within the local setting.  The present study was aimed to investigate hematological and serum biochemical changes in cysticercosis infested cattle and buffaloes. For this purpose, 60 cysticercosis seropositive animals (n=30 buffaloes; n=30 cattle) and 60 cysticercosis seronegative animals (n=30 buffaloes, n=30 cattle) based on ELISA were used. These animals were selected from private abattoir from November 2012 to October 2013.  Blood and serum sample were collected from these animals and were tested for hemogram and serum biochemical profile using automated hematology and biochemistry analyzers, respectively. The results showed a significant (P<0.05) decrease in hemoglobin and platelet count while other hematological parameters like RBCs, WBCs, MCV, MCH and MCHC remained non-significant (P>0.05). Among serum biochemistry characters, minerals and glucose did not differ significantly (P>0.05). Significant decrease (P<0.05) was observed for total serum protein, cholesterol, and aspartate transaminase enzyme in infested animals. It was concluded that cysticercosis has deleterious effects on hemogram and serum biochemical profile of cattle and buffaloes.
Keywords: Cysticercosis; bovine; hematological; cholesterol; serum protein